1999
DOI: 10.1159/000028326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-(N,N-Dimethyl)-Amiloride, a Specific Inhibitor of Na<sup>+</sup>/H<sup>+</sup> Exchanger, on the Palmitoyl-<i>L</i>-Carnitine-Induced Mechanical and Metabolic Derangements in the Isolated Perfused Rat Heart

Abstract: The present study was carried out to determine the effect of 5-(N,N-dimethyl)-amiloride (DMA), a specific inhibitor of the Na+/H+ exchanger, on the cardiac mechanical and metabolic derangements induced by palmitoyl-L-carnitine (PALCAR). Rat hearts were perfused aerobically at a constant flow according to the Langendorff technique, while being paced electrically. PALCAR (5 μmol/l) increased the left-ventricular end-diastolic pressure, decreased the left ventricular developed pressure (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…The content of long-chain acyl carnitines (including PC) increases in myocytes during hypoxia (DaTorre et al, 1991), and these molecules are reported to accumulate in sarcolemmal membranes (Knabb et al, 1986). Although the concentration of PC in ischemic myocardial cells has not been reported to our knowledge and the effects of endogenously produced and exogenously applied PC may be different, the concentration of 4 M PC used in this study is similar to concentrations used in previous studies (Mészà ros and Pappano, 1990;Sato et al, 1992;Wu and Corr, 1992;Shen and Pappano, 1995;Arakawa et al, 1997;Arakawa and Hara, 1999;Netticadan et al, 1999;Maruyama et al, 2000), and the effects of an exogenous application of 4 M PC in this study are similar in magnitude to the effects of brief ischemia associated with a 4-to 5-fold elevation of long-chain acyl carnitine content in the heart (DaTorre et al, 1991). Thus, the results of the present study suggest that a pathologically enhanced, PC-induced late I Na may be a contributor to ischemia-induced dysfunction.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The content of long-chain acyl carnitines (including PC) increases in myocytes during hypoxia (DaTorre et al, 1991), and these molecules are reported to accumulate in sarcolemmal membranes (Knabb et al, 1986). Although the concentration of PC in ischemic myocardial cells has not been reported to our knowledge and the effects of endogenously produced and exogenously applied PC may be different, the concentration of 4 M PC used in this study is similar to concentrations used in previous studies (Mészà ros and Pappano, 1990;Sato et al, 1992;Wu and Corr, 1992;Shen and Pappano, 1995;Arakawa et al, 1997;Arakawa and Hara, 1999;Netticadan et al, 1999;Maruyama et al, 2000), and the effects of an exogenous application of 4 M PC in this study are similar in magnitude to the effects of brief ischemia associated with a 4-to 5-fold elevation of long-chain acyl carnitine content in the heart (DaTorre et al, 1991). Thus, the results of the present study suggest that a pathologically enhanced, PC-induced late I Na may be a contributor to ischemia-induced dysfunction.…”
Section: Discussionsupporting
confidence: 58%
“…An increase of late I Na in the heart is known to lead to Na ϩ and Ca 2ϩ overload and both electrical and mechanical dysfunction (Ver Donck et al, 1993;Hale et al, 2008). Several agents are reported to attenuate the toxic effects of PC on the isolated heart: the Na ϩ channel blockers tetrodotoxin (TTX) and dilazep , the Na ϩ /H ϩ exchange inhibitor 5-(N,N-dimethyl)-amiloride (Arakawa and Hara, 1999), and the local anesthetic, lidocaine . These findings suggest that inhibition of Na ϩ channels and reduction of sodium overload are beneficial to reduce PC-induced dysfunction.…”
mentioning
confidence: 99%
“…1A, there was a minor but statistically significant influence of pH on GlySar permeability in wild-type mice, with the optimal uptake being at pH 5.5. To further examine this relationship, increasing concentrations of dimethylamiloride (DMA), a Na ϩ /H ϩ exchange inhibitor (Arakawa and Hara, 1999;Mirossay et al, 1999), were added to perfusate containing GlySar to disrupt the naturally occurring proton gradient. As observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 ) and is obviously rather unspecific. Four different inhibitors of sodium channels [20,21] inhibited potassium transport in both WT and Δ kdpA ; in particular, 5‐( N , N ‐dimethyl)‐amiloride (DMA) and quinidine were highly effective. In striking contrast, all four compounds had no effect in the Δ ntpJ strain.…”
Section: Resultsmentioning
confidence: 99%